Towards K‐Ion and Na‐Ion Batteries as “Beyond Li‐Ion” - Kubota, Kei; Dahbi, Mouad; Hosaka, Tomooki; Kumakura, Shinichi; Komaba, Shinichi (Chemical record, 2018)
Li‐ion battery commercialized by Sony in 1991 has the highest energy‐density among practical rechargeable batteries and is widely used in electronic devices, electric vehicles, and stationary energy storage system in the world. Moreover, the battery market is rapidly growing in the world and further fast‐growing is expected. With expansion of the demand and applications, price of lithium and cobalt resources is increasing. We are, therefore, motivated to study Na‐ and K‐ion batteries for stationary energy storage system because of much abundant Na and K resources and the wide distribution in the world. In this account, we review developments of Na‐ and K‐ion batteries with mainly introducing our previous and present researches in comparison to that of Li‐ion battery. Li‐ion battery commercialized by Sony in 1991 has the highest energy‐density among rechargeable batteries and is widely used in the world. With expansion of the applications and rapid growing of the battery market, price of lithium and cobalt resources is increasing. In this account, we review developments of Na‐ and K‐ion batteries, consisting of much abundant Na and K, with mainly introducing our previous and present researches in comparison to that of Li‐ion battery.